Seasonal Variation in Content and Chemical Composition of Essential Oils from Leaves of Mentha longifolia Huds. (Lamiaceae) - Nikšić, Haris; Kovač-Bešović, Elvira; Durić, Kemal; Korać, Nermina; Omeragić, Elma; Muratović, Samija (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
The aim of the present study was to appraise variation in content and the chemical composition of essential oil from the leaves of Mentha longifolia as affected by harvesting season. Quantities of the essential oils were determined according to the European Pharmacopoeia 4th Ed. and chemical profiles by using a gas chromatography – mass spectrometry. The highest content of the essential oil was found plant during the flowering stage (1.9%). The main constituents of the essential oil through all the three phenophases were oxygened monoterpenes piperitone oxide (1.9-63.6%) and 1,8-cineole (5-12%), and sesquiterpenes trans-caryophyllene (3-9.3%) and germacrene D (0.16-10%). In general, the composition of the essential oil in all the three investigated phenophases was generally similar with quantitative differences. Oxygenated monoterpenes were dominant during flowering stage and after flowering stage, followed by sesquiterpene hydrocarbons. Presence of β-ocimene, γ-terpinene, and carvone were noticed only before flowering; cederole, β-cubebene and α-caryophyllene during the flowering stage; and 3-carene after flowering. Analysis of the qualitative and quantitative composition of main constituents of the essential oil in all the three investigated phenophases led to the conclusion that the piperitone oxide, as the major compound could be used as the stable chemotype marker for the taxonomy of Mentha longifolia.